Moinhos do Almansor em Montemor-o-Novo: levantamento e interpretação arquitetónica de um património esquecido, como contributo para a sua salvaguarda - Oliveira, Gabriel António Barrenho de (2020)
The purpose of this investigation is to advance the study, systematically and in detail, from a historical and geographic perspective, of the hydraulic mills, and their complementary structures, located in the river Almansor, anciently known as “ribeira de Canha”, in the section between the bridges of Évora and Lisbon (old port of Lisbon). It intends to contribute to the knowledge of this heritage of hydraulic engineering, destined to the grinding of cereals, as to the system of grinding, the materials and constructive techniques. It is the most important of the rivers that cross the region of Montemor-o-Novo, inserted in a dense and intricate water network, profoundly connected to the Monfurado mountain range, belonging to the hydrographic basins of the Tagus and Sado rivers. It runs from East to West, from its source in Arraiolos, in the estate of Almansor, to the confluence in the river Sorraia, affluent of the Tagus. Along the way, it gathers the streams of other watercourses, and bypasses the town of Montemor-o-Novo along the south side of its haunting hill top castle. It is here that all the watermills analyzed for this study are located, powered by the energy of the river that also served the irrigation of the surrounding orchards and fruit gardens. Once the most important element in a prolific relationship between people and the landscape, the river was slowly forgotten, as was its cultural significance, and is now covered with dense vegetation, and is difficult to access. The current investigation intends to contextualize these windmills within their relation with the territory. Beginning in the system of catchment and conduction of water, the transformation of energy into movement, the surrounding built environment and finally the accesses – that can range from a simple pathway or road, a cross at a ford, a proper river port and stepping stone passages. All the watermills surveyed for this study employ a horizontal water-wheel system. Their construction usually adopted an elongated plan, with one or two floors, elevated through thick low grade walls, and a plain rooftop sustained by wooden structures and traditional ceramic tiles. Rendered obsolete by the technological advancements of the 20th Century, most of these watermills are currently in a state of abandonment and ruin. This research intends to reflect on the problematic of this built heritage, which is in danger of being forever lost, in the attempt to define a critical approach to value and safeguard these structures, advancing examples of rehabilitation that can be used as reference for a future strategy of renewal; RESUMO: Esta investigação tem como objectivo o estudo aprofundado, através do levantamento sistemático, pormenorizado e enquadrado, do ponto de vista histórico, geográfico e arquitectónico dos moinhos hidráulicos e estruturas complementares de apoio ao seu funcionamento, localizados no Rio Almansor, antiga ribeira de Canha, no troço entre as pontes de Évora e de Lisboa (antigo Porto de Lisboa). Pretende contribuir para o conhecimento deste património de carácter hidráulico, destinado à moagem de cereais, quanto ao sistema de moagem, aos materiais e técnicas construtivas. É a mais importante das ribeiras que atravessam o concelho, inserida numa densa e recortada rede hídrica, associada à serra de Monfurado, pertencente às bacias hidrográficas do Tejo e do Sado. Corre de este para oeste, desde a nascente em Arraiolos, na herdade de Almansor, à confluência no rio Sorraia, afluente do Tejo. Reúne os caudais de outras ribeiras e contorna a vila pelo lado sul na aproximação a esta, onde se concentram a totalidade dos moinhos analisados, fornecia- -lhes energia, ao mesmo tempo que irrigava as hortas e os pomares adjacentes ao longo do seu curso. Outrora estruturante a infraestrutura hidráulica encontra-se, agora, coberta de densa vegetação e de difícil acesso. A presente investigação, pretende contextualizar os Moinhos e a sua relação com o território. Que começam no sistema de captação e condução da água, à transformação da energia em movimento, às estruturas de apoio e finalmente aos acessos – que podem ser uma simples calçada ou carreiro, a um atravessamento a vau ou um porto regularizado e alpondras de pedras fincadas em linha. Os moinhos levantados são da tipologia de roda motriz horizontal (moinhos de rodízio), de abastecimento por cubo. São de base alongada em planta, com um ou dois pisos, a cobertura era de duas pendentes e era executada em ripado simples de pinho ou choupo e revestida com telha de canudo. O sistema construtivo de referência, baseia-se em alvenaria ordinária de junta argamassada e rebocada. O estado actual da maioria dos moinhos é de abandono e ruina. Esta investigação pretende reflectir sobre a problemática deste património edificado, que está em vias de desaparecer, e definir uma abordagem que vise a sua salvaguarda e valorização, apresentando alguns exemplos de reabilitação, que poderão servir de referência.